Asian English
XV, 325 p. 3 illus., 2 illus. in color.
Keywords: Contesting the idea that the study of Anglophone literature and literary studies is simply a foreign import in Asia, this collection addresses the genealogies of textual critique and institutionalized forms of teaching of English language and literature in Asia through the 19th and 20th centuries, along with an examination of how its present options and possible future directions relate to these historical contexts. It argues that the establishment of Anglophone literature in Asia did not simply “happen”: there were extra-literary and -academic forces at work, inserting and domesticating in Asian universities both the English language and Anglo-American literature, and their attendant cultural and political values. Offering new perspectives for ongoing conversations surrounding the globalization of Anglophone literature in literary and cultural studies, the book also considers the practicalities of teaching both the language and its canon of classic texts, and that thehistorical formation and shape of English studies in Asia offers lessons that relate not only to the discipline but also may be applied to the humanities as a whole.